Party Quotas and Gender Differences in Candidate Experience in Australia: 1987–2016. Issue 2 (29th November 2021) - Beauregard, Katrine; Taflaga, Marija
Abstract: While previous investigations have demonstrated that legislative gender quotas can disrupt traditional recruitment networks to level women's and men's political experience, little is known about the impact of party quotas. Using the Australian Candidate Survey, we find that gender party quotas can help close the experience gap between male and female candidates, but also between women. Before the adoption of party quotas, Coalition female candidates had more experience than Labor female candidates. This party gap disappears along with gender gaps amongst Labor candidates after the Labor Party adopted gender quotas. We find that party quotas made little impact on the experience levels of male Labor candidates or Coalition candidates' of both sexes. We identify the professionalisation of politics and women-centric networks as factors shaping how quotas impact candidate selection processes.